Experimental Study of Natural Convective Flow over a Hot Horizontal Rhombus Cylinder Immersed in Water via PIV Technique - M. Karbasi pour; M. Nili-Ahmadabadi; G. Taherian; A. Minaean (Journal of Applied Fluid Mechanics, 2017)
Natural convective flow over a horizontal cylinder is a phenomenon used in many industries such as heat transfer from an electrical wire, heat exchanger, pipe heat transfer, etc. In this research, fluid dynamics of natural convective flow over a horizontal rhombus cylinder, with uniform heat flux, is investigated by using two-dimensional Particle Image Velocimetry (PIV) Technique. Experiments are carried out in a cubical tank full of water having an interface with air and the cylinder is placed horizontally inside the tank. The heater is turned on for 40s and the effects of heater's power and the height of water above the cylinder are surveyed. The experiments are carried out in three different heights of water and two different heater’s powers in which Rayleigh number changes from 1.33×107 to 1.76×107. The emitted heat flux causes the buoyancy force to be made and the main branch of flow to be formed. Then, moving up the main branch flow through the stationary water generates two equal anti-direction vortexes. These vortexes are developed when they reach the free surface. The results indicate that the flow pattern changes for different values of water height and heater’s power.